Argentina, road leading to Mount Olivia near Ushuaia - Forman, Harrison, 1904-1978 (1954)
Forman 0178 c1: Approach to Mt. Olivia (elev. 4,495 ft) which overlooks Ushuaia, Argentina - world's southernmost town - at the stinger-tip of South America, less than 450 miles from Antarctica. Argentina: Tierra del Fuego Grayscale Forman Safety Negatives, Box 24